Factors controlling the temporal variability of mercury in runoff from seven catchments in Northern and Southern Sweden - Kraus, Andrea (SLU/Dept. of Aquatic Sciences and Assessment, 2011)
The increased input of anthropogenic mercury in the environment has led to the accumulation of mercury (Hg) in the aquatic food chain and poses serious problems to the ecosystem and human health. Time series data from May 2004 – May 2010 in three catchments in northern (Balsjö) and from October 2006 – 2009 in four catchments in southern (Örebro) Sweden associated with different forest treatments (e. g. clear cut, site preparation) were assessed to determine the influence of different factors on the temporal pattern of total organic carbon (TOC), total mercury (THg) and methylmercury (MeHg). Mean THg and MeHg concentrations varied in Balsjö between 4.92 – 5.48 and 0.39 – 0.47 ng/L and between 5.60 – 10.36 and 0.90 – 1.71 ng/L in Örebro. MeHg mean concentrations peaked in all catchments during summer period coinciding with maximum biological activity and were associated with low flow conditions. Analyzing THg concentrations over all seasons it was found that they also peaked in summer, however, the concentrations were more attributed to high flow in Balsjö and to low flow in Örebro. Site SP in Örebro had the highest export of MeHg, THg and TOC in this study (19.49 µg/d*ha, 137.89 µg/d*ha and 405.50 g/d*ha). In Balsjö, THg concentrations showed a good correlation with flow, whereas the THg-flow relationship had no significant importance in Örebro. The Riparian Profile Flow-Concentration Integration Model (RIM) was used to show controls over TOC, MeHg and THg stream concentration in the different catchments. The RIM achieved highest Nash-Sutcliff (NS) coefficients at all sites after adding a seasonal component to the simulations. The RIM simulated soil solution profiles for the sites in Örebro and Balsjö supported the results gained from time series and soil dry fraction analysis. This study highlighted the importance of different drivers for the seasonal variation in THg and MeHg concentrations. The results indicated that the Balsjö sites were more flow driven, whereas the catchments in Örebro were characterized by a strong seasonal pattern. Furthermore, the high importance of antecedent flow and temperature on THg and MeHg concentrations (Past Least Square (PLS) analysis) highlighted the influence of the watershed conditions prior to an event. Across all sites, it was shown that organic matter was the number one factor explaining total mercury dynamics. In Örebro 54 – 85 % and in Balsjö 62 – 72 % of the variation in THg concentrations could be explained by TOC.